Gender and sexuality in the culture war: conservatism on WhatsApp - SOUZA, Aknaton Toczek; Rosa, Pablo Ornelas (Argumentum, 2023)
This article analyses the discussions on gender and sexuality produced during the Brazilian hyper-militarisation process. It stems from an investigation conducted using the ethnographic method involving WhatsApp groups self-identifying as conservative and Christian, and who directly supported President Jair Bolsonaro. It analyses the role of gender and sexuality studies in the militarisation process, and in its resurgence due to neoliberal reasoning. It then presents an investigation of the 2018 elections and the government of Jair Bolsonaro, verifying how the propagation of the notion of a culture war came to be used to confer a certain legitimacy in its increasingly vehement actions in relation to its political opponents. Finally, it reveals, through ethnographic and documentary data, how gender and sexuality studies began to be mobilised in this war, serving as moral justification for political and economic purposes. Keywords: Digital platforms. Gender. Sexuality. War. Social representations.